Struktur dan Pengendalian Internal Organisasi Pengelola Zakat - Wardy Putra, Trisno (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2019)
This study aims to examine the internal structure and control of zakat management organizations. The potential for zakat which reaches 217 trillion is a great potential if it is managed professionally. The method used is a qualitative method that comes from various literatures. The results of the study indicate that the need for an organization's internal structure and control to maintain the transparency of zakat management institutions.